2014
DOI: 10.5005/jp-journals-10008-1152
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Optical Coherence Tomography Changes to the Anterior Chamber Angle in the Short-term following Laser Peripheral Iridoplasty

Abstract: Purpose: To evaluate, by anterior segment optical coherence tomography (AS-OCT), the changes in the anterior chamber angle during the short-term postoperative period after diode laser peripheral iridoplasty (LPI).Methods: Retrospective, observational study of consecutive primary angle closure suspect, primary angle closure, or primary angle closure glaucoma patients who underwent LPI. These patients had persistent iridotrabecular contact despite the presence of a patent peripheral iridotomy.The AS-OCT images o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“… 18 23 - 25 In the setting of persistent occludable angles after iridotomy, we previously documented that in the short term, additional iri-doplasty brings about significant widening of the ACA. 16 This study does not report on gonioscopic findings as the aim was to quantify changes in angle configuration using AS-OCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 18 23 - 25 In the setting of persistent occludable angles after iridotomy, we previously documented that in the short term, additional iri-doplasty brings about significant widening of the ACA. 16 This study does not report on gonioscopic findings as the aim was to quantify changes in angle configuration using AS-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous other studies have also reported iridoplasty as safe with no significant associated complications. 16 25 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Существует множество доказательств значительного увеличения УПК после лазерной иридотомии и лазерной иридопластики при заболеваниях закрытого угла передней камеры по различным параметрам, полученным с помощью AS-визуализации [44][45][46][47][48][49][50][51][52]. При сравнении результатов лазерной иридотомии и факоэмульсификации с имплантацией ИОЛ дополнительная оценка эффективности лечения возможна с использованием ОКТ переднего отрезка для определения ширины УПК [53].…”
Section: визуализация переднего отдела глаза в оценке эффективности лечения болезни закрытого углаunclassified
“…LPIp is a safe and simple operation, which can effectively open the closed angle [ 6 ]. At present, different spot locations, spot numbers, and energy levels are used according to the personal experience and preference of the ophthalmologist.…”
Section: Introductionmentioning
confidence: 99%